Measuring the kinetics of calcium binding proteins with flash photolysis - Faas, Guido C.; Mody, Istvan (Biochimica et biophysica acta, 2012)
Calcium-binding proteins (CBPs) are instrumental in the control of Ca2+ signaling. They are the fastest players within the Ca2+ toolkit responding within microseconds to [Ca2+] changes. The CBPs compete for Ca2+ which plays a direct role in modulating Ca2+ transients and the resulting biochemical message. The kinetic properties of the CBPs have to be known to have a good understanding of Ca2+ signaling. Most techniques used to measure binding kinetics are too slow to accurately determine the fast kinetics of most CBP. Furthermore, many CBPs bind Ca2+ in a cooperative way, which should be incorporated in the kinetic modeling. Here we will review a new ultra-fast in vitro technique for measuring Ca2+ binding properties of CBPs following flash photolysis of caged Ca2+. Compartmental modeling is used to resolve the kinetics of fast cooperative Ca2+ binding to CBPs. Currently this technique has only been used to quantify the kinetics of three CBPs (calbindin, calretinin and calmodulin), but has already provided remarkable insights into the specific role that these kinetics in Ca2+ signaling. The potential to gain novel insights into Ca2+ signaling by quantifying kinetics of other CBPs using this technique is very promising. This article is part of a Special Issue entitled Biochemical, biophysical and genetic approaches to intracellular calcium signaling. ► Kinetics of Ca2+ binding proteins (CBPs) are too fast to gauge with normal methods. ► The fast kinetics of CBPs can be determined using flash photolysis. ► Cooperativity should be included when quantifying binding kinetics of CBPs. ► The binding kinetics of CBPs play a key role in calcium signaling.